2014
DOI: 10.1007/s10549-014-3212-3
|View full text |Cite
|
Sign up to set email alerts
|

Stearidonic acid-enriched flax oil reduces the growth of human breast cancer in vitro and in vivo

Abstract: The 20 and 22 carbon n-3 long-chain polyunsaturated fatty acids (LCPUFA) inhibit the growth of tumors in vitro and in animal models, but less is known about the 18 carbon n-3, stearidonic acid (SDA). This study aimed to establish and determine a mechanism for the anti-cancer activity of SDA-enriched oil (SO). SO (26 % of lipid) was produced by genetically engineering flax and used to treat human tumorigenic (MDA-MB-231, MCF-7) and non-tumorigenic (MCF-12A) breast cells. Nu/nu mice bearing MDA-MB-231 tumor were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 66 publications
(95 reference statements)
1
14
0
Order By: Relevance
“…The concentration of AA in breast tumors has been reported to be directly associated with tumorigenesis , suggesting a mechanism for effects on cell survival. However, we have previously demonstrated that treating MDA‐MB‐231 cells with a mixture of fatty acids containing SDA (26%) and DGLA (15%) reduced survival of MDA‐MB‐231 cells despite a 25% increased content of AA in cellular PL . Similar to our findings for both SDA and ETA, treatment with SDA has been reported to increase the content EPA and DPA in MDA‐MB‐231 cells .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The concentration of AA in breast tumors has been reported to be directly associated with tumorigenesis , suggesting a mechanism for effects on cell survival. However, we have previously demonstrated that treating MDA‐MB‐231 cells with a mixture of fatty acids containing SDA (26%) and DGLA (15%) reduced survival of MDA‐MB‐231 cells despite a 25% increased content of AA in cellular PL . Similar to our findings for both SDA and ETA, treatment with SDA has been reported to increase the content EPA and DPA in MDA‐MB‐231 cells .…”
Section: Discussionsupporting
confidence: 89%
“…Our study demonstrates that all of the n‐3 (SDA, ETA) and n‐6 (GLA and DGLA) fatty acid intermediates reduced the survival of tumorigenic but not non‐tumorigenic MCF‐12A cells. It has been found that treatment of MDA‐MB‐231 cells with SDA (50–200 μM) reduced cell survival more effectively than ALA and this was associated with a greater reduction in COX‐2 protein and mRNA levels , and we previously demonstrated that feeding a diet containing 0.8% w/w SDA reduced the growth of MDA‐MB‐231 tumors implanted in nu/nu mice . Similarly, feeding SDA (3% w/w) reduced mammary tumor growth in the APC (min/+) mouse .…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…It is tempting to speculate that intracellular metformin acts on tumor fatty acid metabolism potentially to alleviate proliferative n-6 series ligands (AA or its derivatives), and enrich n-3 series ligands (LNA or its derivatives) that can oppose proliferation. Indeed, dietary n-3 supplementation increased mammary tumor phospholipids containing n-3 PUFA, concomitantly with decreased phospholipid AA, resulting in decreased tumor growth in vivo (49). At present, we do not understand if this observation is dependent on HFD consumption, or if metformin might generally affect the balance of n-6 and n-3 FA only in OCT2 positive mammary tumors.…”
Section: Discussionmentioning
confidence: 99%